Assessment of Knowledge, Attitude, and Practice on Level of Awareness Among Pediatric Emergency Department VisitorsMakkah City, Saudi Arabia: Cross-Sectional Study - A. Alruzaiza, Samah; M. Mahrous, Rasha (International Journal of Psychosocial Rehabilitation, 2020)
Emergency department (ED) is one of the vital and critical areas inside the hospital. Most of the time, it has been over-utilized in providing the essential care services that could be provided by the Primary Healthcare Centers (PHCCs), especially from the pediatric population. Therefore, this research aimed to assess parents’ knowledge, attitudes, and practices about healthcare services. A cross-sectional, descriptive study conducted to measure the knowledge, attitudes, and practices of parents regarding their choice to come to ED over the PHCCs at Maternity and Children Hospital – Pediatric Emergency Department in Makkah, from the 3rd to 14th of March, 2020. Data was collected through self-administered KAP questionnaire in English/Arabic languages completed by the parents. A total of 402 Saudi and non-Saudi parents with a child aged 0 – 15 years have participated in this study. The majority of the respondents were Saudis (91.5%), mothers (67.9%), employed (71.9%), uninsured (73.6%), and (14.7%) of their children suffered from a chronic disease. The most common reason for preferring EDs was the quality of the provided services (49.5%). Multi sociodemographic characteristics such as parents’ nationality, education level, employment status, relation to the child, gender of the child and if the child has a chronic disease were significantly associated with parents’ knowledge, attitudes, and practices. The study presented inadequate parental knowledge of alternative healthcare services and low levels of professional educational activities. Comprehensive parental education programs are essential to enhance medical care and developing strategies to implement policies aimed to reduce the nonurgent use of EDs is highly recommended.